Successful immune checkpoint blockade in a patient with advanced stage microsatellite-unstable biliary tract cancer - Busch, Elena; Kloor, Matthias; Goeppert, Benjamin; Fröhling, Stefan; Uhrig, Sebastian; Weber, Tim; Meinel, Jörn; Sutter, Christian; Weiss, Karl Heinz; Schirmacher, Peter; Knebel Doeberitz, Magnus von; Jäger, Dirk; et al. (Cold Spring Harbor molecular case studies, 2017)
Cancers acquire multiple somatic mutations that can lead to the generation of immunogenic mutation-induced neoantigens. These neoantigens can be recognized by the host's immune system. However, continuous stimulation of immune cells against tumor antigens can lead to immune cell exhaustion, which allows uncontrolled outgrowth of tumor cells. Recently, immune checkpoint inhibitors have emerged as a novel approach to overcome immune cell exhaustion and reactivate antitumor immune responses. In particular, antibodies blocking the exhaustion-mediating programmed death receptor (PD-1)/programmed death receptor ligand (PD-L1) pathway have shown clinical efficacy. The effects were particularly pronounced in tumors with DNA mismatch repair (MMR) deficiency and a high mutational load, which typically occur in the colon and endometrium. Here, we report on a 24-yr-old woman diagnosed with extrahepatic cholangiocarcinoma who showed strong and durable response to the immune checkpoint inhibitor pembrolizumab, although treatment was initiated at an advanced stage of disease. The patient's tumor displayed DNA MMR deficiency and microsatellite instability (MSI) but lacked other features commonly discussed as predictors of response toward checkpoint blockade, such as PD-L1 expression or dense infiltration with cytotoxic T cells. Notably, high levels of HLA class I and II antigen expression were detected in the tumor, suggesting a potential causal relation between functionality of the tumor's antigen presentation machinery and the success of immune checkpoint blockade. We suggest determining MSI status in combination with HLA class I and II antigen expression in tumors potentially eligible for immune checkpoint blockade even in the absence of conventional markers predictive for anti-PD-1/PD-L1 therapy and in entities not commonly linked to the MSI phenotype. Further studies are required to determine the value of these markers for predicting the success of immune checkpoint blockade. An open-access, peer-reviewed, international journal in the field of precision medicine. Articles in the journal present genomic and molecular analyses of individuals or cohorts alongside their clinical presentations and phenotypic information.